Peran Nadzir Dalam Pengelolaan Tanah Wakaf Ditinjau Dari Perspektif Undang-Undang Nomor 41 Tahun 2004 (Studi Kasus di Desa Ngadi Kec. Mojo Kab. Kediri) - Fachrodin (Institut Agama Islam Negeri (IAIN) Kediri, 2020)
Target in this research is: to analyse the duty nadzir in management of land ground communal ownership; To analyse the role nadzir in management of land; ground communal ownership Countryside Ngadi evaluated from in perpective Number Law 41 Year 2004; For the describe of factors influencing role nadzir in management of land; ground communal. Research conducted Countryside of Ngadi of Subdistrict of Mojo of Regency Kediri. this Research Type field research. Population to be checked as above mentioned hence the sample is nadzir exist in Countryside of Ngadi Kec. Mojo Kab. Kediri. As for data source in this research, is source of data of primary and source of data secondary. Technique of data collecting use the interview, observation, and documentation. Result of this research is: Duty nadzir in management of land; ground communal ownership Countryside of Ngadi Kec. Mojo Kab. Kediri have the duty such as those which loaded section 11 Law No 41 Year 2004; Management communal ownership by nadzir Countryside of Ngadi Kec. maximal Uncommitted Mojo its meaning nadzir which ought to undertake to manage and manage 12 land; ground communal ownership in the reality sharing do not at all, and land; ground communal ownership managed by one management (non nadzir).